Analisis Wacana Kritis Citra Inklusif Dedi Mulyadi di YouTube - Rezzi Nanda Barizki; Hiswanti Hiswanti; Iswahyu Pranawukir (Universitas Prof. Dr. Moestopo (Beragama), 2026)
This study examines Dedi Mulyadi’s self-representation through a grounded, humanistic communication style enriched with Sundanese cultural symbols on his YouTube channel. The urgency of this research lies in understanding contemporary discursive practices that combine local narratives, cultural values, and netizen participation in shaping leadership images in the era of digital democracy. This study aims to analyze the discursive construction of Dedi Mulyadi’s communication style on social media and the image of an inclusive leader formed through symbolic interaction, visual content, and personal narratives. Using Fairclough’s Critical Discourse Analysis model, data were collected through observations of content uploaded on Kang Dedi Mulyadi Channel from April to July 2025 and netizen comments. The findings show that simple diction and Sundanese cultural symbols are strategically used to blur class boundaries between elites and citizens. Non-protocol content production functions as a political communication strategy to control public narratives. At the social practice level, this phenomenon reflects digital populism that appears egalitarian but continues to reproduce asymmetric power relations, paternalistic hegemony, and patron-client culture.